Understanding the role of dogs (Canis lupus familiaris) in the transmission dynamics of trypanosoma cruzi genotypes in Colombia (2013)
The dog (Canis lupus familiaris) is the most important domestic reservoir of Chagas disease, a zoonosis that affects more than 10 million people in Latin America. Trypanosoma cruzi, the etiologic agent of the disease, displays remarkable genetic variability, as indicated by its six genotypes (TcI-TcVI). A pilot study was conducted to establish the prevalence of T. cruzi among the canine population by analyzing 80 dogs. We report the identification of the TcI, TcII, TcIV and TcVI genotypes as single infections. TcI/TcII and TcI/TcIV presented as mixed infections and included the presence of Trypanosoma angel. The implications of this distribution are herein discussed. Based on the molecular epidemiology findings, this study suggests a plausible role for canine synanthropism in the transmission of T. cruzi.